Ліквідація «іоаннітського» руху в 1920–1950-х рр. на Вінниччині - Логінов, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
By the example of «Ioanit» movement, the methods used by state security service to struggle the religious underground were investigated.